Amaranth protein isolates modified by hydrolytic and thermal treatments. Relationship between structure and solubility - Scilingo, Adriana Alicia (2002)
Structure and solubility of modified amaranth isolates were studied. Isolates were obtained from proteolytic (cucurbita or papain) and/or thermal treatments of an amaranth isolate. Results showed that 11S-globulin and globulin-P, the main targets for the proteases, were hydrolyzed more efficiently by papain than by cucurbita. Thermal treatment induced both aggregation and dissociation of proteins. Dissociation increased with hydrolysis. It was also shown that polymers and globulin molecules were responsible for the insolubility of a non-treated isolate and that their hydrolytic modification made the isolate more soluble. While a thermal treatment decreased the isolate solubility, a previous hydrolysis with papain increased the solubility. Consequently, the amaranth isolate hydrolyzed with papain is a suitable ingredient in foods submitted to thermal treatment considering that it keeps a high solubility after heating.